Formação de formadores: um estudo de caso a partir da disciplina de EAD do Curso de Pedagogia da FACED/UFC - Souza, Talita Alves Soares de (2023)
The present work sought to analyze teaching mediation in distance education, bringing, as an example, the contributions of the training of trainers who work in the distance education discipline of the Pedagogy course at FACED/UFC. The research methodology is qualitative in nature with a bibliographic survey and interviews with trainers from the UFC Pedagogy course, through the analysis of reports from the institution's trainers and highlighting how the Fedathi Sequence can contribute to a more dynamic and reflective distance education. The guiding question of the research is: what contribution does the Fedathi Sequence methodological proposal offer in the training of trainers who work in the distance learning discipline of the Pedagogy course at FACED/UFC? The general objective was to analyze how the Fedathi Sequence contributes to the training of trainers who worked in the distance learning discipline of the Pedagogy course at FACED/UFC. The specific objectives were: to briefly describe what research says about the concept of cyberculture; investigate the advances in distance learning in Brazil and the proposed UAB model; present the characteristics of the Fedathi Sequence methodological proposal in teaching mediation. The chapters are divided into: introductory chapter, in chapter two, the methodological path of the research is presented. In chapter three, we discuss the concept of cyberculture based on Castells (1999), Lévy (1999) and then more on theoretical discussions and the creation of the UAB as a way of institutionalizing distance learning in Brazil, also discussing the role of the tutor. In the following chapter, we present the Fedathi Sequence as a methodology proposal for the distance learning discipline offered by the FACED/UFC Pedagogy course based on Borges Neto (2017; 2018), Torres (2014), Soares (2017), among others and finally, the analysis of the research data and the final considerations. From the results, we can infer that this research contributes not only to the FACED-UFC Pedagogy Course, but to rethink the model of tutoring training in undergraduate courses with a focus on mediation with active participation of students in the construction of knowledge, be a model for various courses offered through EaD.